Experimental evolution reveals habitat‐specific fitness dynamics among Wolbachia clades in Drosophila melanogaster. Issue 4 (February 2014) - Versace, Elisabetta; Nolte, Viola; Pandey, Ram Vinay; Tobler, Ray; Schlötterer, Christian
Abstract The diversity and infection dynamics of the endosymbiont Wolbachia can be influenced by many factors, such as transmission rate, cytoplasmic incompatibility, environment, selection and genetic drift. The interplay of these factors in natural populations can result in heterogeneous infection patterns with substantial differences between populations and strains. The causes of these heterogeneities are not yet understood, partly due to the complexity of natural environments. We present experimental evolution as a new approach to study Wolbachia infection dynamics in replicate populations exposed to a controlled environment. A natural Drosophila melanogaster population infected with strains of Wolbachia belonging to different clades evolved in two laboratory environments (hot and cold) for 1.5 years. In both treatments, the rate of Wolbachia infection increased until fixation. In the hot environment, the relative frequency of different Wolbachia clades remained stable over 37 generations. In the cold environment, however, we observed marked changes in the composition of the Wolbachia population: within 15 generations, one Wolbachia clade increased more than 50% in frequency, whereas the other two clades decreased in frequency, resulting in the loss of one clade. The frequency change was highly reproducible not only among replicates, but also when flies that evolved for 42 generations in the hot environment were transferred to the cold environment. These results document how environmental factors can affect the composition of Wolbachia in D. melanogaster. The high reproducibility of the pattern suggests that experimental evolution studies can efficiently determine the functional basis of habitat‐specific fitness among Wolbachia strains.